Pilomatricoma masquerading as a parotid mass in a child-a diagnostic challenge on cytology - Dr. Kadam Maruthi Vijaya; Dr. Mukunda Pai Malathi; Dr. Premalatha Chennagiri S; Dr. Biswas Siddhartha (Tropical Journal of Pathology and Microbiology, 2017)
Pilomatrixoma is a slow growing benign skin neoplasm of hair matrix origin. This tumor is common in children and young adults, especially in the head and neck region. Because of its varied morphological spectrum on cytology it can pose diagnostic difficulties and cause unnecessary treatment. We report a case of 5 year old girl who presented with a nodule over right parotid region. Fine needle aspiration cytology was done which was suspicious of mucoepidermoid carcinoma; however, histopathological diagnosis was Pilomatrixoma. On review of literature we observed that pilomatricomas have been quite often misdiagnosed especially on cytology. Our case highlights the diagnostic pitfalls of pilomatricoma on cytology.